Raising Students’ Motivation and Learning Interest Through Discipline: SMP Negeri 1 Barru Context - Abdul Kahar Yunus; Nurafiyat Ekamurti (LPPM Universitas Lancang Kuning. Pekanbaru. Indonesia, 2020)
This study aims to examine how the application of discipline to improve students’ motivation and learning interest at SMP Negeri 1 Barru. The sample in this quantitative study was taken through proportional random sampling. Based on the results of the study, it can be concluded that there is a significant influence of the application of discipline to the increase of students’ motivation and learning interest at SMP Negeri 1 Barru. This can be seen in the significance value of the value of tcount and ttable namely tcount (3.5) is higher than ttable (1.99). The strength of the influence of the application of discipline to students' motivation and interest in learning at SMP Negeri 1 Barru reached 0.4 level, which means it is in a good category